2006
DOI: 10.1186/1471-2458-6-308
|View full text |Cite
|
Sign up to set email alerts
|

Is the HIV burden in India being overestimated?

Abstract: Background: The HIV burden estimate for India has a very wide plausibility range. A recent population-based study in a south Indian district demonstrated that the official method used in India to estimate HIV burden in the population, which directly extrapolates annual sentinel surveillance data from large public sector antenatal and sexually transmitted infection (STI) clinics, led to a 2-3 times higher estimate than that based on population-based data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 7 publications
5
18
0
Order By: Relevance
“…Nonetheless, data collection is generally performed through prenatal health services, considered sentinel sites, and nonrandom selection of health establishments can substantially affect results. In India, HIV prevalence found in a populationbased study was much lower than that obtained through a sentinel study of prenatal clinics [11]. On the other hand, incomplete coverage of the sentinel network in African countries, which fail to reach rural and remote areas, can underestimate HIV prevalence in these countries [12].…”
mentioning
confidence: 84%
“…Nonetheless, data collection is generally performed through prenatal health services, considered sentinel sites, and nonrandom selection of health establishments can substantially affect results. In India, HIV prevalence found in a populationbased study was much lower than that obtained through a sentinel study of prenatal clinics [11]. On the other hand, incomplete coverage of the sentinel network in African countries, which fail to reach rural and remote areas, can underestimate HIV prevalence in these countries [12].…”
mentioning
confidence: 84%
“…Four hundred ANC attenders from each of the two ANC in all of Karnataka's 27 districts were sampled each year between 2003 and 2007 inclusive. Although it has been suggested that HIV prevalence among ANC attenders in India may overestimate HIV prevalence in the general population [17], the fact that the same sites and populations were sampled over a period of many years allows for an examination of trends over time [18].…”
Section: Methodsmentioning
confidence: 99%
“…Most HSS-ANC sites are located in and around urban district headquarters, and coverage of rural areas, where more than 70% of the population reside [10], is limited. In fact, as in other countries [11], studies in India have shown that HSS-ANC sites overestimate HIV prevalence in the general population [12], [13]. Second, because of the limited number of sites in each district (generally two), analysis of HIV prevalence at the sub-district level is not possible.…”
Section: Introductionmentioning
confidence: 96%